Pengaruh Indikator Makro Ekonomi, Kinerja Keuangan, Dan Tata Kelola Terhadap Nilai Perusahaan Pada Sektor Properti Di Bursa Efek Indonesia - Muhamad Sugiarto; Perdana Wahyu Sentosa (Universitas YARSI, 2018)
This study analyzes the influence of macro economic factors, the company's performance and governance on firm value. The variables studied were the BI interest rate, the rupiah against the US Dollar, ROE, TATO, Leverage, the use of big four public accounting, and managerial ownership, and Tobin's Q. This study uses panel data models Random Effect. As a result, studies show that the interest rate BI, the rupiah against the US Dollar, ROE, TATO, Leverage, the use of public accountants big four, and managerial ownership together significantly affect firm value represented by the variable Tobin's Q. Partially, BI interest rate, the rupiah against the US Dollar, ROE, and TATO significant effect on the value of the company, while the leverage, the use of the big four public accounting firms, and managerial ownership has no significant effect on firm value.